The views and attitudes of general practitioners and smokers toward provision of smoking cessation advice: a qualitative study - Cleland, Jennifer (Prim Care Respir J, 2004)
OBJECTIVES: To identify common themes between general practitioners (GP's) and patients on smoking cessation in primary care in order to inform the development of acceptable guidelines, thus maximising the chance that recommendations will be received positively and implemented. DESIGN: Qualitative study using focus groups and individual interviews with GPs and patients. SETTING: North East Scotland. SUBJECTS: 10 general practitioners and 20 patients (10 smokers and 10 patients who described themselves as ex-smokers). RESULTS: Both general practitioners and patients agreed that the GP has a key role in providing a range of advice and support for smoking cessation. Both parties expressed views at variance with current guidelines but agreed that, for support and advice to be successful, it needs to comply with four of the five main themes identified; that it should be practical, pertinent to the consultation, personalised to the smoker's clinical need, and should emphasise the positive health gains from quitting. CONCLUSION: The considerable concordance between the perceptions of GPs and their patients about smoking cessation care suggests potential for a more positive partnership in working towards reduction of smoking in the UK.